Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1590/s0100-204x2016000900011
|View full text |Cite
|
Sign up to set email alerts
|

Eutrofização de solos e comunidade arbórea em fragmentos de uma paisagem agrícola

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da eutrofização do solo em fragmentos remanescentes de vegetação nativa sobre a comunidade florística de arbóreas em paisagens agrícolas. Foram amostrados oito sítios de vegetação arbórea na Mata Atlântica, no Estado do Rio de Janeiro, em pares formados de acordo com o uso do solo em seu entorno -intensivo (UI) ou extensivo (UE) -e com diferentes tamanhos: dois fragmentos pequenos, com cerca de 10 ha; dois médios, com 30 ha; dois grandes, com 100 ha; e out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Among the potential impacts from surrounding agricultural areas on the interior of the fragments, changes in soil fertility with increased nutrient levels have been widely discussed in the literature [15,17,18,47]. A recent study in the same study site [18] showed a trend of soil eutrophication in forest fragments located in the same study area, with significant increases in calcium, phosphorus and potassium, while another similar study [17] observed that the higher the fertilizer application intensity in agricultural areas, the higher the nutrient content in nearby forest fragments. The frequent practices of liming and fertilizer use in conventional agriculture fields combined with soil rotation result in drift and transport of fine soil particles by air, which are deposited in soil fragments [15,17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the potential impacts from surrounding agricultural areas on the interior of the fragments, changes in soil fertility with increased nutrient levels have been widely discussed in the literature [15,17,18,47]. A recent study in the same study site [18] showed a trend of soil eutrophication in forest fragments located in the same study area, with significant increases in calcium, phosphorus and potassium, while another similar study [17] observed that the higher the fertilizer application intensity in agricultural areas, the higher the nutrient content in nearby forest fragments. The frequent practices of liming and fertilizer use in conventional agriculture fields combined with soil rotation result in drift and transport of fine soil particles by air, which are deposited in soil fragments [15,17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Location of the studied fragments and land use classes in the Guapi-Macacu River Basin, Rio de Janeiro, Brazil (FIDALGO et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations